Characterization of chemical constituents and rats metabolites of Shuanghua Baihe tablets by HPLC‐Q‐TOF‐MS/MS. (11th June 2014) - Zheng, Lu; Cong, Haijian; Xue, Ming; Xiang, Ting; Yao, Zhongqing; Wu, Bin; Lin, Wenhui
ABSTRACT A high‐performance liquid chromatography/quadrupole time‐of‐flight mass spectrometry method was established to detect as many constituents in rat biological fluids as possible after oral administration of Shuanghua Baihe tablets (SBT). An Agilent Poroshell 120 EC‐C18 column was adopted to separate the samples, and mass spectra were acquired in positive and negative modes. First, the fingerprints of SBT were established, resulting in 32 components being detected within 40 min. Among these compounds, 12 were tentatively identified by comparing the retention times and mass spectral data with those of reference standards and the reference literature; the other 20 components were tentatively assigned solely based on the MS data. Furthermore, metabolites in rat plasma and urine after oral administration of SBT were also analyzed. A total of 19 compounds were identified, including 13 prototypes and six metabolites through metabolic pathways of demethylation and glucuronide conjugation. Glucuronidated alkaloids were the main constituents in the plasma, and were then excreted from urine. This is the first systematic study on the metabolic profiling of SBT. Copyright © 2014 John Wiley & Sons, Ltd.